Symmetries and Dynamics of Star Clusters - Haas, Jaroslav; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
In this PhD thesis, which was nominated for publication in this series by the Astronomical Institute at Charles University, Prague, the author investigates the orbital evolution of an initially thin stellar disc around a supermassive black hole, considering various perturbative sources of gravity. His findings, obtained by both direct numerical N-body modelling and using standard perturbation methods, offer a viable theoretical explanation for the observed configuration of young stars in the Galactic Centre. This marks a significant contribution to a topic of great interest in contemporary astrophysics. The author also shows in his thesis that a secular instability (m = 1 mode) may occur in the embedding spherical cluster of old stars. This increases the richness of possible evolution scenarios of the embedding cluster and may lead to effective feeding of supermassive black holes through tidal disruption of stars on extremely eccentric orbits.
Foreword -- Prerequisities -- Disc embedded in spherical cluster -- Coupling of near-Keplerian orbits -- Sagittarius A* -- Conclusions.
Keywords: Physics; Physics; Astrophysics and Astroparticles; Theoretical, Mathematical and Computational Physics